PENGARUH PEMBERIAN ASAM HUMAT DAN ZEOLIT TERHADAP PERTUMBUHAN TANAMAN TOMAT (Solanum lycopersicum L.) VARIETAS SERVO F1 - Novia Alfiana; Rika Yayu Agustini; Devie Rienzani Supriadi (Universitas Tribhuwana Tunggadewi, 2026)
Tomato (Solanum lycopersicum L.) is a high-value horticultural commodity, yet its productivity in Indonesia tends to fluctuate. Efforts to increase production can be made by improving soil physical and chemical properties using soil conditioners. Humic acid enhances nutrient availability but requires a carrier, such as zeolite, for optimal distribution. This study aimed to determine the most effective dosage combination of humic acid and zeolite on the vegetative growth of the tomato variety. Servo F1. The research was conducted in an open field in Purwakarta, West Java, from April to August 2025. A single-factor Randomized Complete Block Design (RCBD) was used with 6 treatments and 4 replications, resulting in 24 experimental units. The treatments consisted of combinations of humic acid (25, 50, 75 L/ha) and zeolite (500, 750 kg/ha). Parameters observed included plant height, leaf number, and stem diameter at 14, 21, 28, and 35 days after transplanting (DAT). Data were analyzed using ANOVA, followed by DMRT, at ? = 5%. The results showed that the combination of 50 L/ha humic acid and 750 kg/ha zeolite produced the highest values for all observed parameters. At 35 DAT, Treatment the combination of 50 L/ha humic acid and 750 kg/ha zeolite resulted in plant height (109.76 cm), leaf number (150.50), and stem diameter (10.86 mm). It is concluded that the combination of 50 L/ha humic acid and 750 kg/ha zeolite effectively enhances the vegetative growth of the tomato variety. Servo F1 is recommended as a soil amendment.